COVID-19: review of case reports - Oda, Yutaka (J Anesth, 2020)
Recently published case reports relating to anesthesia in patients with coronavirus disease (COVID-19) were reviewed. The diagnosis of COVID-19 was confirmed by positive results of reverse transcriptase polymerase chain reaction test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Numerous reports handled emergency cesarean delivery. Primary symptoms and laboratory data of pregnant women with COVID-19 were similar to those of non-pregnant patients. Although the mortality rate is reported to be high after surgery in patients with COVID-19, cesarean delivery was successfully performed under regional anesthesia in most cases and postoperative course was favorable both in the parents and newborns. There is no direct evidence of vertical mother-to-child transmission of SARS-CoV-2; however, a diagnosis of COVID-19 was made in a newborn two hours after delivery from a pregnant woman with COVID-19, based on the increased immunoglobulin levels and deranged liver function, suggesting that its possibility cannot be completely eliminated. Emergency cerebral shunt reconstruction was performed repeatedly in an eight-month-old boy with COVID-19. The tracheal tube was removed in the operating room after surgery and postoperative course was uneventful. All the procedures should be performed in isolated operating rooms with medical staff with level-3 personal protection to ensure the safety of patients and health care providers.